Uji Akurasi Rasd Al-Qiblat Global Sebagai Metode Penentuan Arah Kiblat - Shofwatul Aini (Fakultas Syariah, Universitas Islam Negeri Raden Mas Said Surakarta, 2022)
One of the methods to determine easily and accurately the qibla direction is by using the shadow of thing that leads to qibla direction. This method in Islamic astronomy is called as Raṣd al-Qiblat, and it has two kinds: that is, global and local Raṣd al-Qiblat. The focus in this study is the global Raṣd al-Qiblat. This method is chosen since it does not need the process of counting first, unlike the local Raṣd al-Qiblat. This global Raṣd al-Qiblat happens twice a year, on 28 May at 16:18 WIB and on 16 July at 16:27 WIB. The time taken in this study is on 16 July at 16:27 WIB. The problem raised in this study is how the accuracy of global Raṣd al-Qiblat as a method to determine the qibla direction, and how the limitation of time for the accuracy of this method applied in Indonesia. It can be concluded in this study that first, the global Raṣd al-Qiblat is an accurate method in determining the qibla direction. The Global Raṣd al-Qiblat on 16 July in 2022, 2023, and 2024 at 16:27 WIB with range ± 3 minutes is an accurate time for determining qibla direction. The most accurate time for global Raṣd al-Qiblat on 16 July 2022 for the western region of Indonesia or Java is at 16:25 WIB, on 16 July 2023 is at 16:26 WIB, and on 16 July 2024 is at 16:24 WIB.